Proses dan Etika Mujadalah dalam Al-Qur’an sebagai Pendekatan Komunikasi Dakwah - Fakhri Yusuf; Yusran Nasir; Rasyidah; Siti Maisarah; Jailani Ahmad (Kalam: Jurnal Agama dan Sosial Humaniora, 2025)
This paper aims to find out the mujadalah communication approach in the Al-Qur'an. In writing, a qualitative descriptive communication approach is used with content analysis. The information collection method or technique uses library research, where library research is investigate is the movement of collecting materials related to inquire about beginning from books, journals, literature and other publications. There are two sources of data, namely primary data comes from the Al-Qur'an and Tafsir, and secondary data comes from books and other publications. The research results show that the word mujadalah comes from the Arabic "Jādala", while the fi'il mudhari' means "Yujādilu", "Mujadalah" which means to argue or debate and can also be interpreted as discussion or dialogue. The Qur'an regulates the ethics of mujadalah or discussion, including in Surah An-Nahl (125), Surah Al-Hajj (3), and Surah Al-Ankabut (46). The interpretation of this verse gives rise to the ethics of carrying out discussions or debates, namely by good wisdom, including good delivery procedures, polite language, arguments based on science and facts, and respecting the dignity of the discussion partner so that communication goals can be achieved and provide positive feedback. Penelitian ini mengkaji konsep mujadalah dalam Al-Qur’an sebagai basis nilai etika komunikasi Islam, serta relevansinya dalam komunikasi modern, termasuk pada platform digital dan media sosial. Dengan menggunakan metode studi pustaka (library research), pendekatan tafsir, komunikasi Islam, etika Islam, dan hermeneutika, penelitian ini menganalisis ayat-ayat Al-Qur’an yang berkaitan dengan mujadalah, di antaranya QS. An-Nahl: 125, QS. Al-Hajj: 3, dan QS. Al-Ankabut: 46. Hasil penelitian menunjukkan bahwa mujadalah dalam Al-Qur’an bukan sekadar debat, tetapi dialog persuasif yang menekankan hikmah, kejujuran, kesopanan, penghargaan terhadap lawan bicara, serta argumentasi berbasis ilmu. Nilai-nilai tersebut sejalan dengan prinsip komunikasi efektif, karena mendukung terciptanya komunikasi yang diterima, dipahami, dan membangun umpan balik yang positif. Penerapan nilai mujadalah sangat relevan dalam ruang publik digital untuk menghadapi tantangan komunikasi di era informasi, termasuk dalam upaya mencegah disinformasi, ujaran kebencian, dan konflik daring. Penelitian ini merekomendasikan internalisasi nilai mujadalah dalam praktik dakwah, pendidikan, dan komunikasi sosial, baik di ruang konvensional maupun digital.